2020
DOI: 10.5937/ijcrsee2002059p
|View full text |Cite
|
Sign up to set email alerts
|

Economic Implications of Education in Southeast Europe

Abstract: This research covers an evaluation of the impact of education system, educational, scientific and other institutions on the economic growth in nine countries of Southeast Europe (SEE). The main hypothesis is the following: GDP pc growth is significant and positively correlates with the indicators of the state of education system. In addition to educational institutions, there are other social and economic indicators on which education and science depend, namely the budget and fiscal system, corruption and prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 23 publications
(24 reference statements)
0
1
0
Order By: Relevance
“…Their results suggest that elements of science and the quality of higher education greatly affect the size of GDP per capita in the studied countries. Similar research was carried out in South-Eastern Europe by Popović et al (2020). The authors focused on assessing the impact of the education system, educational, scientific, and other institutions on economic growth in nine countries of South-Eastern Europe (SEE) and concluded that indicators of the state of educational and other institutions are positively correlated with GDP per capita growth.…”
Section: Literature Overviewmentioning
confidence: 93%
“…Their results suggest that elements of science and the quality of higher education greatly affect the size of GDP per capita in the studied countries. Similar research was carried out in South-Eastern Europe by Popović et al (2020). The authors focused on assessing the impact of the education system, educational, scientific, and other institutions on economic growth in nine countries of South-Eastern Europe (SEE) and concluded that indicators of the state of educational and other institutions are positively correlated with GDP per capita growth.…”
Section: Literature Overviewmentioning
confidence: 93%